2000
DOI: 10.1046/j.1365-8711.2000.03380.x
|View full text |Cite
|
Sign up to set email alerts
|

The entropy and energy of intergalactic gas in galaxy clusters

Abstract: Studies of the X-ray surface brightness profiles of clusters, coupled with theoretical considerations, suggest that the breaking of self-similarity in the hot gas results from an `entropy floor', established by some heating process, which affects the structure of the intracluster gas strongly in lower mass systems. Fitting analytical models for the radial variation in gas density and temperature to X-ray spectral images from the ROSAT PSPC and ASCA GIS, we derive gas entropy profiles for 20 galaxy clusters and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

37
269
4

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 217 publications
(310 citation statements)
references
References 57 publications
37
269
4
Order By: Relevance
“…However, all of these estimated energies for SNe are based on the assumption of thermal winds. If the wind velocity were ∼ 3 times larger than the escape velocity more energy could be gained by the ICM (see Lloyd-Davies et al 2000). …”
Section: Model Resultsmentioning
confidence: 99%
“…However, all of these estimated energies for SNe are based on the assumption of thermal winds. If the wind velocity were ∼ 3 times larger than the escape velocity more energy could be gained by the ICM (see Lloyd-Davies et al 2000). …”
Section: Model Resultsmentioning
confidence: 99%
“…Early measurements of the entropy based primarily on ROSAT and ASCA data indicated that groups had flatter entropy profiles than cluster scale objects (David et al 1996), and measurements of the entropy at 0.1 R 200 revealed an entropytemperature (K − T ) relation that was shallower than expected (Ponman et al 1999;Lloyd-Davies et al 2000;Ponman et al 2003). These data also afforded the first indications for excess entropy above that expected from gravitational collapse even at large radius in group-scale objects (Finoguenov et al 2002;Ponman et al 2003).…”
Section: Introductionmentioning
confidence: 95%
“…A definitive evidence of breaking of self-similarity is the entropy excess (the "entropy floor") detected in the core of cool systems with a baseline entropy of about 70−140 keV cm 2 (Ponman et al 1999;Lloyd-Davies et al 2000). The origin of this break of similarity is not yet understood.…”
Section: Entropy and Non-gravitational Heatingmentioning
confidence: 99%